Research on the Joint Clearing Model for Energy Storage Participation in Electricity and Frequency Regulation Markets - Wang Miao; Liu Gang; Zhao Qingsong; Wang Zhonghui; Li Jiaze; Wang Mingkai (E3S Web of Conferences)
With the large-scale integration of renewable energy and the deepening reform of electricity marketization, the role of energy storage technology in power systems has become increasingly prominent. Energy storage not only addresses the mismatch between renewable energy output and peak load demand but also provides ancillary services such as frequency regulation and reserve capacity, enhancing grid stability and reliability. This paper establishes a joint clearing model for energy storage participation in electricity and frequency regulation markets, optimizing power resource allocation through market-oriented mechanisms, leveraging the performance advantages of energy storage systems, and improving electricity market efficiency. A case study based on a 39-node system integrated with energy storage devices verifies the feasibility and effectiveness of the proposed model. The results demonstrate that the joint clearing mechanism can reduce system marginal costs, increase the utilization frequency of energy storage, and simultaneously meet the dual requirements of electricity supply and frequency regulation services.